Effect of Mesenchymal Stem Cell-Derived Exosomes on Retinal Injury: A Review of Current Findings - Raffaele Nuzzi; Paolo Caselgrandi; Alessandro Vercelli (Stem Cells International)
In recent years, various studies have followed in the literature on the therapeutic effects of mesenchymal stem cells (MSC) on damage in retinal cells. The evidence that MSCs exert their regenerative and damage reduction effect in a paracrine way, through the release of soluble factors and exosomes, is now consolidated. Exosomes are microvesicles formed by a double layer of phospholipid membrane and carry proteins and RNA, through which they play a therapeutic role on target cells. Scientific research has recently focused on the use of exosomes derived from MSC in various models of retinal damage in vitro and in vivo as they, compared to MSCs, have similar functions and at the same time have different advantages such as greater stability and handling, a lower chance of immunological rejection and no risk of malignant transformation. The purpose of this review is to summarize current knowledge on the therapeutic use of exosomes derived from MSCs in retinal damage and to stimulate new clinical perspectives regarding their use.